VARIASI PENGGUNAAN PASIR BESI PADA CAMPURAN MORTAR - Fitro Darwis; Mufti Amir Sultan; Demi Sidogu (Journal of Science and Engineering, 2018)
Iron sand is a natural resource that many found in North Maluku one of them in Yao Village District Morotai Island. Iron sand mining results have the potential to become an Indonesian commodity but iron sand processing is still not maximized at this time. The purpose of this research is to know whether the sand of Yao Village including iron sand, To know the effect of iron sand usage as fine aggregate on the mortar mixture against compressive strength and against absorption. In this research, the test of compressive strength and mortar absorption. This research uses fine aggregate substitution material is Yao Village sand. Preparation of specimen with Fas 0,40, Yao Village sand composition as substitution of fine aggregate that is 0%, 20%, 40%, 60%, 80% and 100% to the fine aggregate weight. The composition of Sand Yao Village after the most dominant purification was Fe (75.84%) of the total iron ore content, followed by Si, Ti, Ca, Al, and other minor elements, so it was classified as an iron sand. There is a decrease in compressive strength along with the increase of iron sand composition 0%, 20%, 40%, 60%, 80% and 100%. Large decreases in compressive strength of each s 19.20 MPa, 19.00 MPa, 18.60 MPa, 13.00 MPa, 13.00 MPa and 12.36 MPa. absorption of mortar in 20% iron sand substitution and 40% of absorption increased, at 60% composition decreased.